1998
DOI: 10.1159/000014308
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Hemorheological and Biochemical Parameters after Plasma Perfusion Using a Tryptophan-Polyvinyl Alcohol Adsorber Leading to Clinical Improvement in Patients Suffering from Maculopathy

Abstract: Background: Selective adsorption is an extracorporeal treatment able to reduce high-molecular-weight proteins and lipids. We evaluated its efficacy in lowering hemorheological parameters to achieve a better microcirculation of the retina. Patients and Methods: Ten patients suffering from maculopathies of various origin underwent a selective plasma adsorption procedure using the TR-350. Plasma and whole blood viscosity, erythrocyte aggregation and proteins and lipids were determined before and 24 h after therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The results of the present study show a clear association between high molecular weight protein and lipoprotein alterations by MDF and the biophysical properties of the plasma. The present study and several previous studies demonstrated that MDF is able to improve the macular function in patients with AMD (12,14–20). Thus, the question arises whether the effects of MDF on COP may contribute to the observed functional results.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results of the present study show a clear association between high molecular weight protein and lipoprotein alterations by MDF and the biophysical properties of the plasma. The present study and several previous studies demonstrated that MDF is able to improve the macular function in patients with AMD (12,14–20). Thus, the question arises whether the effects of MDF on COP may contribute to the observed functional results.…”
Section: Discussionsupporting
confidence: 82%
“…These treatment strategies had in common the elimination of high molecular weight proteins and lipids by extracorporeal treatment procedures especially by membrane differential filtration resulting in an improvement of hemorheological parameters (12,13). Pilot studies and recent randomized trials demonstrated a functional improvement in patients with AMD (12,14–20). The aim of the present study was to investigate the effect of MDF on the plasma COP in patients suffering from non‐exudative AMD and to clarify its significance to visual function.…”
mentioning
confidence: 99%
“…The response rate of AMD patients to plasmapheresis has varied among reported series (9)(10)(11)(12). Direct comparisons among these reported series, however, are difficult because of the use of different plasmapheresis protocols, plasmapheresis filters, and outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…Through DFPP or PE, blood and plasma viscosity can be reduced with consequent improvements in hemorheology (7); therefore, rheopheresis is an application of DFPP for extracorporeal hemorheotherapy (8). Several papers have demonstrated the safety and efficacy of rheopheresis for the treatment of AMD patients since 1996, especially for those with the dry form and soft drusen (9)(10)(11)(12)(13). We report a patient with dry type AMD in his right eye who received a total of eight sessions of DFPP treatment within 10 weeks.We analyzed parameters representing the clinical efficacy and safety of DFPP for AMD at baseline and at 3, 6, 9, and 12 months after treatment of this patient.…”
mentioning
confidence: 99%